Outdoor Recreation - Physiological and Psychological Effects on Health 2021
DOI: 10.5772/intechopen.91900
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Recreation within the School Setting: A Physiological and Psychological Exploration

Abstract: School recess is a crucial outdoor recreation period to develop health behaviours such as physical activity, social and thinking skills that can track into adulthood. As students in some schools can be immersed in playground recreation opportunities via up to 4200 school breaks during their schooling (three times per day, 5 days per week, 39 weeks per year, 7 years of primary school), the school playground has become an emerging focus for researchers to facilitate important health outcomes. Outdoor recreation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 98 publications
0
0
0
Order By: Relevance
“…The students reported that their participation in the programme boosted their autonomy. This finding is consistent with the suggestions of Hyndman and Wyver (2020), as well as Scarf et al (2018), who claimed that the participation of students in outdoor and adventure activities empowered their autonomy. A rational explanation for the promotion of student autonomy after their participation in schoolyard activities could be the fact that following specific rules was not stressed, as they were provided with the autonomy to plan activities when creating their games.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The students reported that their participation in the programme boosted their autonomy. This finding is consistent with the suggestions of Hyndman and Wyver (2020), as well as Scarf et al (2018), who claimed that the participation of students in outdoor and adventure activities empowered their autonomy. A rational explanation for the promotion of student autonomy after their participation in schoolyard activities could be the fact that following specific rules was not stressed, as they were provided with the autonomy to plan activities when creating their games.…”
Section: Discussionsupporting
confidence: 92%
“…Adventure activities encourage group acceptance and therefore significantly increase bonds between adolescents (Scarf et al, 2018). Students are provided with many opportunities to acquire experience in overcoming difficulties that arise from relationships with their peers (Hyndman & Wyver, 2020). Moreover, adventure or outdoor recreational activities have been positively related to the physical quality of life and relatedness (Mullins, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations